The Use of Humanoid Robots with Multilingual Interaction Skills in Teaching a Foreign Language: Opportunities, Research Challenges and Future Research Directions - Ayse Tuna; Gurkan Tuna (Center for Educational Policy Studies Journal)
Since a humanoid robot does not get tired regardless of how many mistakes a student makes, and because it can be equipped with novel teaching techniques and updated with the most current knowledge, it can be useful for achieving many educational goals. The rationale behind this is that it has been shown in the literature that robots are more useful as teaching aids than computers or other instructional tools, as they can mimic human responses. Furthermore, humans, especially children, prefer robot interaction to other interaction types. Adults generally struggle to learn a foreign language, but this is true of some students, too. With their multilingual interaction capabilities, their ability to provide real-time feedback, and their humanlike physical shape, some types of humanoid robots can be of great assistance to students in learning a foreign language. The use of humanoid robots leads to a personal connection with the students, and this can help overcome issues related to shyness, reluctance, frustration and lack of confidence that may emerge in dealing with a human teacher. Moreover, as humanoid robots can be programmed to know specifically what each individual student needs to learn, they can be quite useful for one-on-one speaking activities. Considering the many possibilities that can be offered by information and communication technology tools, particularly by humanoid robots, this paper reviews the roles and functions of humanoid robots in teaching a foreign language, presents novel approaches in this domain, provides research challenges, and finally outlines future research directions.